The Utilization of Quizizz Learning Media for Learning Basic Education - Ningtyas, Rani Kusuma; Syaodih, Ernawulan (International Conference on Elementary Education, 2021)
This paper aims to describe the use of Quizizz as a learning medium. Learning with the use of technology with the Quizizz application besides being fun, challenging, and interactive will contribute to improving student competence and educator creativity. Quizizz is packaged in learning as part of a presentation of subjects, themes, topics of discussion. Quizizz with content can come from the creativity of educators to review lessons to evaluate the understanding and skills of students in absorbing lessons presented in the form of fun exercises or evaluations and can be done outside and inside the classroom as long as the learning support facilities and infrastructure can accommodate it. This paper is a literature review that digs from various sources, including books, journals, and posts on the internet. The results of this paper show that there is a good influence from the use of Quizizz media on student learning at the basic education level. The conclusion is this paper show that Quizizz can produce learning media that is creative, innovative, and fun so that it needs to be used as a learning medium.